Carotenoids of Lettuce (Lactuca sativa L.) grown on soil enriched with spent coffee grounds - Cruz, Rebeca (2012)
The impact of spent coffee grounds on carotenoid and chlorophyll content in lettuce (Lactuca sativa L. var. capitata) was evaluated. A greenhouse pot experiment was conducted with spent coffee amounts ranging from 0% to 20% (v/v). All evaluated pigments increased proportionally to spent coffee amounts. Lutein and β-carotene levels increased up to 90% and 72%, respectively, while chlorophylls increased up to 61%. Biomass was also improved in the presence of 2.5% to 10% spent coffee, decreasing for higher amounts. Nevertheless, all plants were characterized by lower organic nitrogen content than the control ones, inversely to the spent coffee amounts, pointing to possible induced stress. Collected data suggests that plants nutritional features, with regards to these bioactive compounds, can be improved by the presence of low amounts of spent coffee grounds (up to 10%). This observation is particularly important because soil amendment with spent coffee grounds is becoming increasingly common within domestic agriculture. Still, further studies on the detailed influence of spent coffee bioactive compounds are mandatory, particularly regarding caffeine.